Aprendendo a ser e a conviver: práticas colaborativas e dialógicas no contexto escolar - Paschoal, Valéria Nicolau (2016)
This study is characterized as a research-action, resulting from the claim of a school interested in providing the possibilities of perception wideness and a characterization that the teachers have from their students, which many times they are marked by negative and depreciative denotations. It was developed through collaborative and dialogic practices, which were brought to create a space that would enable the improvement of relationships in the scholar environment. According to UNESCO (2016), education must be integrated and humanist through the development of competencies to reach the living in society, becoming a viable way to enable people to respond to the transformations and challenges of present times. The four pillars of education for the 21st century – learn to know, learn to make, learn to be and to live together – they need to be incorporated in the implementation of the educational programs of the schools. The search for a construction of a conversational context organized for the promotion of new types and qualities of connections between teachers-students and students-students evidencing two pillars that represent the social function of a school: which are learning to be and learning to live together, started from the four pillars concept and was based on the social constructionism ideas and on the narrative and collaborative practices. Since this is a research-action, the research made use of procedures which were adapted to each of its four phases including: a free meetings and an interview with the curator; meetings with the teachers; meetings with the parents or with those responsible for the student; workshops of selfknowledge and reflective processes with students and teachers; feedbacks from all participants; and assessment meetings with teachers. The parts who took part of this research are: the curator, six teachers from the 1st to the 5th teaching course, one teacher assistant, ten children (from the age of seven to ten), their parents/or those responsible for them and the school group. The intervention made didn’t intend to find out a new problem and to resolve it, but it did have the proposition of building together with the participants new ways to be and to live together, re-affirming the social function of the school and its commitments with the transformation of the current reality. The narratives generated from this experience, were analyzed according to the social poetics and they were organized, being considered as arresting moments, around four categories: the effects of the collaborative and dialogic practices in the scholar context; considerations about the function of the school and their teachers in the 21st century; the collaborative posture in the implementation of such practices; and the development of the research through the planning of new actions. The application of this model to the scholar context was proved to be viable and useful for the construction of a more agreeable environment encouraging people to be together, mainly for the fact that it talks about values and because it triggers thoughts and attitudes to be reviewed, giving visibility to aspects of the participants’ life that weren’t noticed by them before the application of this experience